Do big four auditors always provide higher audit quality? Evidence from Pakistan - Ammar Abid; Muhammad Shaique; Muhammad Anwar ul Haq (International Journal of Financial Studies, 2018)
The purpose of this paper is to examine the role of external auditors in potentially approving or limiting a firm's earnings management practices in institutional settings which do not provide incentives for auditors to deliver high audit quality. We use signed discretionary and performance-adjusted discretionary accruals as proxies for earnings management, and audit firm size (Big 4 vs. Non-Big 4) and audit opinion type (Qualified vs. Unqualified) as measures for audit quality. Using a sample of 183 firms listed on the Karachi Stock Exchange, Pakistan for the five-year period from 2009 to 2013, we find that there is statistically no significant difference between earnings management activities of firms audited by Big 4 and non-Big 4 auditors. Audit opinion is not being issued in response to the earnings management activities being employed by firms. Further consistent with the entrenchment hypothesis, we find that earnings management is pervasive in family controlled firms and Big 4 auditors do not moderate the relation between family firm dominance and earnings management. A small audit market coupled with non-existent litigation risk, strong economic bonding of auditors with their clients, lower investor protection, poor enforcement mechanisms and dominance of firms by influential family groups lead auditors to behave opportunistically, which undermines their independence and objectivity.
Keywords: M49; 330; auditor quality; Big 4 auditors; discretionary accruals; earnings management; family ownership